Lamellar nanoporous gold thin films with tunable porosity for ultrasensitive SERS detection in liquid and gas phase. Issue 23 (5th June 2020) - Chauvin, Adrien; Lafuente, Marta; Mevellec, Jean Yves; Mallada, Reyes; Humbert, Bernard; Pina, Maria Pilar; Tessier, Pierre-Yves; El Mel, Abdelaziz
Abstract : Porous gold lamellar structure with high SERS performance is created by copper chemical etching of a pure gold and pure copper stacked layers. SERS response is recorded for trace level detection of probe molecule in liquid and gas phase. Abstract : Lamellar nanoporous gold thin films, constituted of a stack of very thin layers of porous gold, are synthesized by chemical etching from a stack of successively deposited nanolayers of copper and gold. The gold ligament size, the pore size and the distance between lamellas are tunable in the few tens nanometer range by controlling the initial thickness of the layers and the etching time. The SERS activity of these lamellar porous gold films is characterized by their SERS responses after adsorption of probe bipyridine and naphtalenethiol molecules. The SERS signal is investigated as a function of the bipyridine concentration from 10 −14 mol L −1 to 10 −3 mol L −1 . The higher SERS response corresponds to an experimental detection limit down to 10 −12 mol L −1 . These performance is mainly attributed to the specific nanoporous gold architecture and the larger accessible surface to volume ratio. The lamellar nanoporous gold substrate is explored for sensitive SERS detection of dimethyl methylphosphonate (DMMP), a surrogate molecule of the highly toxic G-series nerve agents. The resultant nanostructure facilitates the diffusion of target molecules through the nanopores and their localization at the enhancing metallic surface leading to the unequivocal Raman signature of DMMP at a concentration of 5 parts per million.